Nonlinear analysis for wing-rock system with adaptive control - Li, Dongyang; Tsourdos, Antonios; Wang, Zhongyuan; Ignatyev, Dmitry (AIAA, 2022)
Introduction The potential of adaptive control in improving the performance and reliability of control systems attracts researchers and engineers from different disciplines. However, the verification and validation of the flight control system regarding the modeling error, uncertainty, disturbance, and time delay is not an easy task due to the inherent nonlinearity of the problem as well as the lack of rigorous analysis tools for nonlinear systems [1–5].